N-Glycosides of indigo, indirubin, and isoindigo: blue, red, and yellow sugars and their cancerostatic activity - Peter Langer (Beilstein Journal of Organic Chemistry)
Indigo, indirubin, and isoindigo derivatives have been used for centuries as pigments. Since the 1990s, a new aspect of the chemistry of this type of compounds is their activity against various types of cancer. N-Glycosides of indigo, indirubin, and isoindigo, blue, red, and yellow sugars, turned out to be of special interest because of their high cancerostatic activity and structural novelty. The present article provides an account on the synthesis and anticancer activity of these compounds.